Idade da menarca, tendência secular e fatores associados : um estudo de base populacional em uma cidade do Sul do Brasil - Balancieri, Adriana Beletato dos Santos (2013)
To evaluate the age of menarche, verify the secular trend and factors associated with early puberty. Methods: A cross-sectional population-based study was conducted with 376 girls (aged 8-15 years) in a city in southern Brazil. Race, gestational age, birth weight, socioeconomic status and child, mother and mother's grandmother's age at menarche were evaluated through systematic sampling, proportional to the size of demographic expansion area. Anthropometric measurements were performed; the z-score of body mass index was calculated and ranked according to the curves of the World Health Organization. The nutrition classification was grouped as underweight (marked thinness + thinness), normal weight and overweight(overweight, obesity and severe obesity) to compare the mean age of menarche. The age at menarche was reported by recall method. It was carried out a descriptive analysis of the variables as well as some tests like: the Student t; ANOVA; Tukey tests; Pearson correlation and multiple regression, with 5% significance. Results: The mean age at menarche was 11.60 ± 1.5 years. Girls are presenting menarche 1.03 ± 1.70 years earlier than their mothers (p <0.0001). The maternal age at menarche (p <0.0001) and overweight (p = 0.0005) were independently associated with the occurrence of menarche. The age of menarche in this population follows the secular trend of anticipation. The maternal age of menarche and overweight influence, but do not explain the whole process. Other factors which were not studied can be contributing to the decline of the age of menarche.